General model of communication research: origin, development, discussion and recommendation / Han Yongqing - Han, Yongqing; Chang Peng, Kee; Mohd Nor, Nurul Lina (Faculty of Communication and Media Studies (FCMS), 2024)
The General Model of Communication was first proposed by Gerbner in 1956, and over the years, scholars have been conducting theoretical and applied research on this model. Fiske reinterpreted and modified Gerbner’s General Model of Communication to form the Modified Gerbner’s General Model of Communication 1982. In 2022, Srivastava and Nisha applied Modified Gerbner’s General Model of Communication to information security research. They revamped this model to form the Revamped Version of Modified Gerbner’s General Model of Communication, which completely opened up the feedback route from the communicator to the audience in all communication links. These models have some superiorities. Gerbner’s General Model of Communication has two advantages. The Modified Gerbner’s General Model of Communication and the Revamped Version of Modified Gerbner’s General Model of Communication inherited the advantages of the Gerbner’s General Model of Communication and added their advantages. However, these models also had a common limitation that did not reflect the meaning generation that the essence lies in the fact that it did not reflect the effect of communication products on the audience. Both the Modified Gerbner’s General Model of Communication and the Revamped Version of Modified Gerbner’s General Model of Communication did not solve the problem, so academia should fully integrate modern communication phenomena based on new media technologies to continue in-depth research into the Revamped Version of Modified Gerbner’s General Model of Communication to overcome its limitation. Therefore, this paper gave a recommendation combined with an ongoing study for future research.